2001
DOI: 10.1590/s0004-282x2001000500011
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes toward epilepsy among primary, secondary and tertiary level teachers

Abstract: -The attitudes toward people with epilepsy are influenced by the degree of knowledge of the condition. Teachers usually do not receive any formal instruction on epilepsy during their training. This study was done to access three hundred teachers knowledge and attitudes toward epilepsy by answering a questionnaire in order to quantify their knowledge, attitude and practice toward epilepsy. Almost all the teachers had heard about epilepsy yet could not demonstrate discrimination among the students. Some teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
3
14

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 15 publications
5
45
3
14
Order By: Relevance
“…Q-5 shows that 77.1% respondents don't know the initial procedure; how to attend and handle a patient during convulsions. These types of studies have been reported [34], that were somewhat comparable. These difficulties were probably due to poor educative programs in epilepsy especially at primary levels.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Q-5 shows that 77.1% respondents don't know the initial procedure; how to attend and handle a patient during convulsions. These types of studies have been reported [34], that were somewhat comparable. These difficulties were probably due to poor educative programs in epilepsy especially at primary levels.…”
Section: Discussionsupporting
confidence: 58%
“…These difficulties were probably due to poor educative programs in epilepsy especially at primary levels. Therefore, services for educational health must be developed in special accordance to epilepsy In remote areas to overcome its consequences as early as possible [34]. People try to avoid communications and physical contact with the patients 15.0% of the respondents assumes that it is contagious or infective, whereas majority (68.4%) showed complete unawareness; Of about 40.1% people were deprived of the knowledge that epilepsy is a chronic neurological disorder and it can't be cured.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in opinion (employment, education, insanity, cause of epilepsy, social attitude) as reflected in polls of 5 year intervals increased during this period 27 . In addition, knowledge and attitudes toward epilepsy among teachers in a Brazilian study showed that although almost all teachers had heard about epilepsy, the knowledge on clinical characteristics and initial procedures to attend a person with epilepsy during a seizure was unsatisfactory 28 . Questions concerning to professional experience in epilepsy also demonstrate lack of information among physical educators.…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan ça-lışmalarda, epilepsi hastalarının hastalıkları hakkında genel toplumdan daha fazla bilgiye sahip olmalarına karşın, klinisyenlerin hastalarının bilgilerini kontrol etmeleri [8] ve hasta ve sağlık personelinin epilepsi hastalığı hakkında devamlı bir eğitime tabi tutulmaları gerektiği bildirilmiştir. [9] Gelişmekte olan [10,11] ve gelişmiş [12,13] ülkelerde ilkokul öğ-retmenleri ile yapılan çalışmalarda öğretmenlerin eğitim oranı ilişkili bulunmamıştır (p>0.05). Hastaların birinci derece yakınlarında epilepsi hastası olması soruların sonuçları için istatistiksel olarak belirleyici faktör değildir (p>0.05).…”
Section: İstatistiksel Analizunclassified